2013
DOI: 10.1002/ajim.22156
|View full text |Cite
|
Sign up to set email alerts
|

Multiple jobholder mortality patterns in Kentucky: An examination of occupational fatalities

Abstract: Increased surveillance of multiple jobholder injuries is needed to improve safety and health on the job. Future investigations should include the relationship between multiple jobholding and agricultural employment as farm owners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Some studies have found that MJH is related to worse health, e.g. higher mortality rates, higher risk of injuries, and higher risk of sickness absence due to mental health problems [1012]. Other studies have found no relation between MJH and health-related outcomes such as long-term sickness absence and absence due to work-related accidents [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that MJH is related to worse health, e.g. higher mortality rates, higher risk of injuries, and higher risk of sickness absence due to mental health problems [1012]. Other studies have found no relation between MJH and health-related outcomes such as long-term sickness absence and absence due to work-related accidents [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…One example of a dual jobholder is a teacher who has an official teaching work during school hours while at the same time engages in official work, maybe holding teaching jobs at night time and weekends (Webster et al, 2018). In various ways, a wider definition of a dual jobholder can be read from the research by Bush, McKee and Bunn (2013), who contextualising it as a person who works more than one job either during day time, night time, weekdays, weekends, multiple full-time jobs, multiple part-time jobs, temporary jobs, self-employment or vice versa.…”
Section: Dual and Multiple Jobholdersmentioning
confidence: 99%
“…The growth of precarious employment, and vulnerable groups such as temporary or undocumented foreign workers, is often concentrated in industries with a high incidence of workplace death, representing a serious challenge for workers’ compensation coverage (Lenore et al, 2004; Guthrie and Quinlan, 2005). More flexible work arrangements, including multiple jobholding, which has been linked to a higher incidence of fatalities (Bush et al, 2013), can complicate the resolution of claims even when coverage is established. There is evidence of significant under-reporting, and failure to lodge or succeed with workers’ compensation claims, even after death or serious injury at work (Sears et al, 2013).…”
Section: Introductionmentioning
confidence: 99%